Sengketa Harta Waris: Tinjauan Perbandingan Hukum Waris Berdasarkan Naskah Hukum Waris - Okinawa, Nurfitri; Wiraja, Asep Yudha (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
The trend of increasing the number of disputes dispute assignment in religious courts at least shows that the dispute over the distribution of the estate remains a special polemic for people's lives. The unification of unruly inheritance was also a contributing factor to the increasing number of petitions of the heir to the court. Indeed, the problem of distribution of intangible assets that is not done fairly will potentially damage fraternity. To avoid such problems, it is necessary to look back at the wisdom of our ancestors in addressing the problems of the inheritance law dispute. One can be found in the manuscript